Mental health and visual acuity in patients with age-related macular degeneration - Cheryl N. Fonteh; Marc T. Mathias; Naresh Mandava; Niranjan Manoharan; Anne M. Lynch; Roxanne Navo; Jennifer L. Patnaik; The University of Colorado Retina Research Group (BMC Ophthalmology, 2022)
Abstract Background Visual acuity (VA) loss has been associated with depression in patients with age-related macular degeneration (AMD). However, previous studies did not incorporate subgroups of AMD when correlating VA and mental health. The goal of this study was to describe the relationship between VA and mental health questions in patients with different classifications of AMD, and to identify associations of mental health subscale scores. Methods AMD patients classified by multi-modal imaging were recruited into an AMD registry. Habitual VA was obtained by ophthalmic technicians using the Snellen VA at distance. At enrollment, patients completed the NEI-VFQ-25, which includes 25 questions regarding the patient’s visual functionality. Median with interquartile-range (IQR) scores on the mental health subscale of the VFQ were calculated by AMD classification and VA groups. Univariate and multivariable general linear models were used to estimate associations between mental health scores and variables of interest. Results Eight hundred seventy-five patients were included in the study. Patients with bilateral geographic atrophy (GA) or bilateral GA and neovascular (NV) AMD scored lowest on the mental health subscales with a median (IQR) of 58.2 (38–88) and 59.3 (38–88). When stratified by VA, patients with a habitual VA of 20/200 or worse scored the lowest on mental health subscales scores: median of 43.8 (IQR: 31–62). Patients with a VA of 20/20 scored the highest: 87.5 (IQR: 81–94). Habitual VA of the better- and worse-seeing eye and AMD classification were significantly associated with mental health subscale scores (all p < 0.0001 in both the univariate and multivariable analysis, except the VA of the worse-seeing eye in multivariable model p = 0.027). Patients enrolled during the COVID pandemic had mental health scores that were 2.7 points lower than prior to the pandemic, but this difference was not significant in univariate (p = 0.300) or multivariable analysis (p = 0.202). Conclusion There is a significant association between mental health questionnaire scores and AMD classification, as well as VA in both the better and worse-seeing eyes in patients with AMD. It is important for clinicians to recognize feelings of worry/ frustration in these patients, so they can be appropriately referred, screened, and treated for mental health problems.